Twin Birth and Maternal Condition - Clarke, D (MIT Press Journals, 2019)
Twin births are often construed as a natural experiment in the social and natural sciences on the premise that the occurrence of twins is quasi-random. We present population-level evidence that challenges this premise. Using individual data for 17 million births in 72 countries, we demonstrate that indicators of mother’s health, health-related behaviors, and the prenatal environment are systematically positively associated with twin birth. The associations are sizable, evident in richer and poorer countries—evident even among women who do not use in vitro fertilization—and hold for numerous different measures of health. We discuss potential mechanisms, showing evidence that favors selective miscarriage. © 2018 by the President and Fellows of Harvard College and the Massachusetts Institute of Technology.